2002
DOI: 10.1177/03635465020300041801
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized Evaluation of Arthroscopic Stabilization versus Nonoperative Treatment in Patients with Acute, Traumatic, First-Time Shoulder Dislocations

Abstract: Arthroscopic stabilization of traumatic, first-time anterior shoulder dislocations is an effective and safe treatment that significantly reduces the recurrence rate of shoulder dislocations in young athletes when compared with conventional, nonoperative treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
335
2
7

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 395 publications
(358 citation statements)
references
References 31 publications
9
335
2
7
Order By: Relevance
“…1 and 2, respectively. Across all six studies, [12][13][14][15][16][17] the arthroscopic surgical treatment showed a decreased rate of recurrent shoulder dislocations or subluxations when compared to the non-operative treatment. Calculated pooled result of NNT was a positive number of 1.76 (95% CI=1.50 to 2.13), indicating that two arthroscopic surgical repairs would need to be performed in order to prevent one recurrent episode.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…1 and 2, respectively. Across all six studies, [12][13][14][15][16][17] the arthroscopic surgical treatment showed a decreased rate of recurrent shoulder dislocations or subluxations when compared to the non-operative treatment. Calculated pooled result of NNT was a positive number of 1.76 (95% CI=1.50 to 2.13), indicating that two arthroscopic surgical repairs would need to be performed in order to prevent one recurrent episode.…”
Section: Resultsmentioning
confidence: 89%
“…According to traumatic or atraumatic classifications, 33) we reviewed and analyzed studies that evaluated patients with firsttime traumatic anterior shoulder dislocations. Therefore, we do not know the effects of the two different interventions on mul- Arciero et al 12) Bottoni et al 13) Jakobsen et al 15) Larrain et al 17) Pooled Kirkley et al 16) DeBerardino et al 14) Fig. 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The complete reading of studies resulted in the exclusion of 7 articles in the German language [14]- [20], 2 studies that did not involve surgical procedures [21] [22], 9 studies without surgical complications [23]- [31], 3 studies comparing the types of sutures [32] [33] [34], 1 study published before 2000 [35] and 1 study with impossibility of access [36]. Through the inclusion and exclusion criteria and after consensus among reviewers, 9 studies were selected to compose the systematic review [37]- [45] (Figure 1).…”
Section: Resultsmentioning
confidence: 99%